Cobalt‐Catalyzed Csp3 −Csp3 Homocoupling. Issue 15 (3rd May 2016) - Cai, Yingxiao; Qian, Xin; Gosmini, Corinne
Abstract: An efficient and easy method for C s p 3 −C s p 3 homocoupling was developed using cobalt bromide as catalyst. A series of functionalized alkyl bromides and alkyl chlorides were coupled in high yields under mild conditions. This reaction seems to involve a radical intermediate. Abstract :